Posterior Nutcracker Syndrome with Left Renal Vein Duplication: A Rare Cause of Haematuria in a 12-Year-Old Boy - J. Preza Fernandes; Rui Amorim; M. J. Gomes; V. Oliveira; A. Reis; J. Ribeiro-Castro (Case Reports in Urology, 2012)
The nutcracker syndrome (NCS) is a rare cause of haematuria. It embraces an extended nonpathognomonic spectrum of symptoms that imply a difficult diagnosis. Ultimately it may be associated with substantial morbidity and even life-threatening events. We report a rare cause if a 12-year-old boy who presented with a history of frequent intermittent episodes of painless constant haematuria. The cystoscopy showed a bloody urine ejaculate from the left ureter meatus. The Doppler ultrasonography showed turbulent pattern of venous blood flow of the posterior renal vein branch behind the aorta. The abdominopelvic computer tomography (apCT) revealed left renal vein (LRV) duplication with a dilated retroaortic branch, entrapped between the aorta and the vertebral column, promoting the renal nutcracker syndrome. The patient was initially hospitalized and managed with oral iron supplements and continuous saline bladder irrigation, not requiring additional treatment. The child is currently asymptomatic, with haemoglobin value returning to normal and therefore proposed to conservative management with close followup. The authors present a case report of episodic haematuria caused by a rare entity—posterior nutcracker syndrome with renal vein duplication.